Indian Ocean variability changes in the Paleoclimate Modelling Intercomparison Project - C. Brierley; K. Thirumalai; E. Grindrod; J. Barnsley (Climate of the Past, 2023)
The Indian Ocean exhibits multiple modes of interannual climate variability, whose future behaviour is uncertain. Recent analysis of glacial climates has uncovered an additional El Niño-like equatorial mode in the Indian Ocean, which could also emerge in future warm states. Here we explore changes in the tropical Indian Ocean simulated by the Paleoclimate Model Intercomparison Project (PMIP4). These simulations are performed by an ensemble of models contributing to the Coupled Model Intercomparison Project 6 and over four coordinated experiments: three past periods – the mid-Holocene (6000 years ago), the Last Glacial Maximum (21 000 years ago), the last interglacial (127 000 years ago) – and an idealized forcing scenario to examine the impact of greenhouse forcing. The two interglacial experiments are used to characterize the role of orbital variations in the seasonal cycle, whilst the other pair focus on responses to large changes in global temperature.